OPEN DEFECATION IN NEPAL A BOX-JENKINS ARIMA APPROACH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Employing annual time series data on the number of people who practice open defecation in Nepal from 2000 – 2017, the study forecasts the annual number of people who will still be practicing open defecation over the period 2018 – 2022. The study applies the Box-Jenkins ARIMA approach. The diagnostic ADF tests show that the series under consideration is an I (1) variable. Based on the AIC, the study presents the ARIMA (2, 1, 0) model as the best model. The diagnostic tests further show that the presented model is stable and its residuals are stationary in levels. The results of the study indicate that the number of people practicing open defecation in Nepal is likely to sharply decline over the period 2018 – 2022, from as high as 19% to as low as 8% of the total population. Therefore, it is very possible to end open defecation in Nepal. In order to significantly sustain this desirable downwards trend, the study suggested a three-fold policy recommendation to be put into consideration, especially by the government of Nepal